Author Correction: Homogeneity evaluation of mesenchymal stem cells based on electrotaxis analysis - Min Sung Kim (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.